2022
DOI: 10.1021/acsnano.2c08649
|View full text |Cite
|
Sign up to set email alerts
|

Significant Suppression of Cracks in Freestanding Perovskite Oxide Flexible Sheets Using a Capping Oxide Layer

Abstract: Flexible and functional perovskite oxide sheets with high orientation and crystallization are the next step in the development of next-generation devices. One promising synthesis method is the lift-off and transfer method using a watersoluble sacrificial layer. However, the suppression of cracks during lift-off is a crucial problem that remains unsolved. In this study, we demonstrated that this problem can be solved by depositing amorphous Al 2 O 3 capping layers on oxide sheets. Using this simple method, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It is suggested that the strain relaxation during the lift-off can be responsible for the formation of cracks, [65] as previously reported in BaSnO 3 membranes. [37] Nevertheless, there are other factors that could be investigated to further reduce the crack density of the released membranes, including the sacrificial layer and membrane thicknesses, [20] the use of additional capping layers [36,64] and modify the lift-off procedure. [35,66] Indeed, the exfoliation process is one of the most critical steps in the preparation of membranes.…”
Section: Freestanding Epitaxial Lsmomentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the strain relaxation during the lift-off can be responsible for the formation of cracks, [65] as previously reported in BaSnO 3 membranes. [37] Nevertheless, there are other factors that could be investigated to further reduce the crack density of the released membranes, including the sacrificial layer and membrane thicknesses, [20] the use of additional capping layers [36,64] and modify the lift-off procedure. [35,66] Indeed, the exfoliation process is one of the most critical steps in the preparation of membranes.…”
Section: Freestanding Epitaxial Lsmomentioning
confidence: 99%
“…[20] It is worth noting that the detachment of a faultless membrane, regardless of the nature of the sacrificial layer, remains a key challenge in the preparation of freestanding films. [35,36] A simple way to modify the properties of SAO is to engineer the metal-oxygen bond through cation substitution. The higher the M 2 + electronegativity (Ca 2 + > Sr 2 + > Ba 2 + ), the lower its bonding ionicity with the nonbridging oxygens of the structure, and thus it is more difficult to hydrolyze.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is very effective in suppressing the generation of cracks in the sheets; therefore, we fabricated crack-free large-area single-crystal oxide sheets used a-Al 2 O 3 as protection layer. 31 Herein, we demonstrate the fabrication of crack-free large-size LBSO sheets with high crystallinity and high orientation through the lift-off and transfer method using SAO and a-Al 2 O 3 as sacrificial and protection layers, respectively. Two types of LBSO sheets, rolled and flat, were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are only a few instances where the ferroelectric properties of BaTiO 3 or BiFeO 3 sheets with approximate sizes of 100 μm have been measured, and the obtained remnant polarization ( P r ) values are relatively small compared to those of bulk materials. ,, Moreover, these sheets exhibit significant current leakage. , To overcome these issues, we proposed the use of an amorphous (a-)­AlO x protection layer before the peeling-off process to obtain large-size crack-free sheets. This technique effectively suppresses crack formation in the sheets. , However, the correlation between the thickness of the a-AlO x layer and the size of the crack-free regions and the selection of an optimal bottom electrode to attain the desired ferroelectric and dielectric properties is still not well understood.…”
Section: Introductionmentioning
confidence: 99%